Training-induced changes in anterior pelvic tilt: potential implications for hamstring strain injuries management - Mendiguchia, J.; De la Flor, A. G.; Mendez-Villanueva, A.; Morin, J.-B.; Edouard, P.; Garrues, M. A. (Journal of Sports Sciences, 2021)
An association has been reported between dynamic anterior pelvic tilt (APT) and hamstring injuries; however, no research has examined if a training-based preventive intervention could alter APT. Therefore, the aim of the present study was to examine if a specific 6-week multimodal intervention, based on the theoretical influence of neighbouring joints and biomechanical interactions between muscles that are inserted to the pelvis, induced changes in APT, during walking gait, hamstring flexibility and trunk endurance. Thirty-five active healthy males volunteered for this single-blind controlled trial and were split into two groups based on baseline data: a control group (CG, n = 20, continued their normal physical activities), and an intervention group (IG, n = 15, performed the intervention programme for 18 sessions over 6 weeks). A significant (p = 0.001) decrease in the APT kinematics during gait, significant increase in the Active Knee Extension Test (p = 0.001), and a significant increase in trunk endurance performance for flexion (p = 0.001), extension (p = 0.001) and side bridge (p = 0.001) were observed, in IG after the 6-week programme, compared to CG.